Prevalence of HIV among women entering labor who accepted or declined voluntary counseling and testing - Theron, Gerhard B. (2012)
OBJECTIVE: To assess whether there was a difference in HIV seroprevalence between eligible women who declined and those who agreed to participate in a study of voluntary counseling and testing among women entering labor with unknown HIV status in South Africa. METHODS: Anonymous cord blood specimens were collected—as dried blood spots—from all women approached for participation in a cluster-randomized trial. No patient identifiers were included on the cord blood specimens. The dried blood spots were analyzed for HIV antibody via enzyme immunoassay and western blotting. RESULTS: Of 7238 women screened for study participation, 1041 (14.4%) had undocumented HIV status; of these women, 542 were eligible for inclusion and 343 enrolled. Based on 513 evaluable samples, the overall seroprevalence was 13.3% (95% confidence interval [CI], 10.4–16.5), which was similar to the 13.1% (95% CI, 9.7–17.2) seroprevalence among the 343 enrolled women. CONCLUSION: Seroprevalence among eligible women was similar to that among enrolled women, which indicates that study participation did not select for a group with an HIV seroprevalence substantially different from that among women who declined to enroll.